eComment. Evidence-based selection of conduits in coronary artery bypass grafting - Özyüksel, Arda; Ersoy, Cihangir; Kayan, Ekin; Akçevin, Atıf (Oxford University Press, 2015)
We read with great interest the article by Gaudino et al. [1]. They have performed coronary artery bypass grafting (CABG) with both internal thoracic arteries (ITA) in a 68-year old patient with a surgical history of aortic coarctation repair. However, there Figure 2: Postoperative angiographic control showing normal functioning left (A) and right (B) ITA grafts. CASE REPORT M. Gaudino et al. / Interactive CardioVascular and Thoracic Surgery 279 Downloaded from https://academic.oup.com/icvts/article-abstract/20/2/279/734665 by guest on 09 April 2020 are some issues we would like to discuss regarding the surgical strategy of the graft selection in this patient. The patient was reported to be hypertensive, both at admission and during the postoperative period. The authors performed a histopathological evaluation of the discarded ITA segments and markedly thickened endothelium was encountered. We wondered how they had decided that the discarded distal segment of the ITA with markedly thickened endothelium guaranteed an intact proximal arterial wall. The atherosclerotic involvement of the ITA may be segmental, hence distal ITA sampling may not accurately predict the degree of atherosclerosis at the proximal part of the graft [2]. Moreover, the same authors had published a review on the use of ITAs in patients with aortic coarctation recently [3]. In that paper, they reviewed 13 reports related to this topic and only one of them included an angiographic control at the long-term follow-up. The authors concluded that, ’a careful evaluation of the conduit is obviously paramount in the context that preoperative transthoracic Doppler ultrasound and selective LITA and RITA catheterization at the time of cardiac catheterization will provide with optimal preoperative planning’.
WOS: 000350199500027
PubMed ID: 25605825
Keywords: eComment; Coronary Artery; Bypass Grafting